The Role of XCR1 and its Ligand XCL1 in Antigen Cross-Presentation by Murine and Human Dendritic Cells - Kroczek, Richard A.; Henn, Volker (Frontiers in Immunology, 2012)
Recently, the chemokine receptor XCR1 has been found to be exclusively expressed on a subset of DC known to be involved in antigen cross-presentation. This review aims to summarize the known biology of the XCR1 receptor and its chemokine ligand XCL1, both in the mouse and the human. Further, any involvement of this receptor-ligand pair in antigen uptake, cross-presentation, and induction of innate and adaptive cytotoxic immunity is explored. The concept of antigen delivery to DC via the XCR1 receptor is discussed as a vaccination strategy for selective induction of cytotoxic immunity against certain pathogens or tumors.